Metafungsi Interpersonal Siberteks Vaksinasi Covid-19: Perspektif Multimodalitas - R. Kunjana Rahardi (Badan Pengembangan dan Pembinaan Bahasa, 2022)
The purpose of this study was to describe the interpersonal metafunctions of the Covid-19 vaccination cybertext in a multimodality perspective. The source of the locational data for this research was the posters of Covid-19 vaccination obtained from google pictures which have been downloaded and acknowledged that their citation was in accordance with applicable scientific procedures, so that they did not conflict with ethical clearance principles of internet-based research. The data of this research were in the form of speeches and graphic images contained in Covid-19 vaccination posters which contain interpersonal metafunctions. Data were collected by reading and taking notes. The method that accommodates the two data collection techniques was the observation method. Data that had been collected properly is selected to separate good data from bad data. Good data were then classified to obtain data types to be subjected to data analysis methods and techniques. Data were validated against relevant experts and theories. The data were analyzed using the extra lingual equivalent analysis method. The matching process was carried out on the extra lingual aspects. The results of this research on interpersonal metafunctions in this multimodality perspective were: (1) Interpersonal metafunctions that provide clarity on the flow of the Covid-19 vaccination, (2) Interpersonal metafunctions that motivate people to undergo Covid-19 vaccination, (3) Interpersonal metafunctions for inviting the success of the Covid-19 vaccination program, (4) Interpersonal metafunctions that provide an explanation for the impact of Covid-19 vaccination, (5) Interpersonal metafunctions invite residents to administer Covid-19 vaccinations. With the findings of metafunction in cybertext through the research, it can be emphasized that interpersonal metafunctions in a multimodality perspective can manifest in various ways. The diversity of these manifestations cannot be separated from technology as a major part of culture which determines the development of language in this new era. AbstrakTujuan penelitian ini adalah mendiskripsikan manisfetasi metafungsi interpersonal teks siber vaksinasi Covid-19 dalam perspektif multimodalitas. Sumber data lokasional penelitian ini adalah poster-poster vaksinasi Covid-19 yang diperoleh dari google pictures yang telah diunduh dan diakui penyitirannya sesuai dengan prosedur ilmiah yang berlaku, sehingga tidak bertentangan dengan prinsip-prinsip etik (ethical clearance) penelitian berbasis internet. Data penelitian ini berupa tuturan dan gambar grafis yang terdapat dalam poster-poster vaksinasi Covid-19 yang di dalamnya terkandung metafungsi interpersonal. Data diperoleh di seputar waktu pelaksanaan penelitian, yakni pertengahan hingga akhir tahun 2021. Data dikumpulkan dengan teknik membaca dan mencatat. Metode yang mewadahi kedua teknik pengumpulan data tersebut adalah metode simak. Data yang telah dikumpulkan dengan baik diseleksi untuk memisahkan data baik dan data nakal atau tidak baik. Data yang baik selanjutnya diklasifikasi untuk mendapatkan tipe-tipe data untuk dikenakan metode dan teknik analisis data. Data divalidasikan kepada pakar dan teori yang relevan. Data dianalisis dengan metode analisis padan ekstralingual. Lanskap pemadanan dilakukan pada aspek-aspek ekstralingualnya. Hasil penelitian metafungsi interpersonal dalam perspektif multimodalitas ini ini adalah: (1) Metafungsi interpersonal pemberi kejelasan alur pelaksanaan vaksinasi Covid-19, (2) Metafungsi interpersonal pemotivasi orang menjalani vaksinasi Covid-19, (3) Metafungsi interpersonal pengajak menyukseskan program vaksinasi Covid-19, (4) Metafungsi interpersonal pemberi penjelasan dampak vaksinasi Covid-19, (5) Metafungsi interpersonal pengajak warga melaksanakan vaksinasi Covid-19. Dengan temuan-temuan metafungsi dalam siberteks tersebut dapat ditegaskan bahwa metafungsi interpersonal dalam perspektif multimodalitas dapat bermanifestasi beragam. Keberagaman manifestasi tersebut tidak lepas dari teknologi sebagai bagian pokok dari budaya yang menjadi penentu perkembangan bahasa di era baru sekarang ini.